Nano-confinement-inspired metal organic framework/polymer composite separation membranes. Issue 33 (11th August 2020) - Li, Xiaoting; Wang, Naixin; Bao, Xinmin; Li, Qian; Li, Jie; Xie, Ya-Bo; Ji, Shulan; Yuan, Jiayin; An, Quan-Fu
Abstract : A new route to engineering a MOF/polymer composite membrane with defect-free, robust and selective layer inside the nano-confinement pores of substrate. Abstract : A defect-free, robust and selective barrier is essential for manufacturing membranes with targeted high permeability and selectivity. Here we report a new route to engineering a separation composite membrane by confining both channels in nanoscale metal organic frameworks (MOFs) and charges in a polyelectrolyte in the inner space of a porous support via a counter-diffusion method. A simple thermal annealing treatment of the interface between the MOF, polymer and support favorably reduced voids inside this nano-confinement environment. As this composite membrane combines both the support and barrier as one, it minimizes mass transfer resistance of water molecules. In a separation test, it readily achieved the state-of-the-art permeance. This simple chemical approach to upgrade membrane structures will offer wide opportunities in separation devices.